THE GLOBAL REFUGEE CRISES: STUDY OF CONTEMPORARY ISSUES AND CHALLENGES - Dr. Rashida Ather (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Through the years, States have affirmed their commitment to protecting refugees by acceding to the 1951 Convention relating to the Status of Refugees and the 1967 protocol at both regional and international level and right to seek asylum has been accepted as a customary principle even then when it comes to protecting refugees many challenges comes to the way such as forcible return back to persecution (refoulement), arbitrary and prolonged detention, lack of access to healthcare, education, and livelihood; sex and gender-based violence; trafficking; and torture. There is a lack of compliance with legal standards. It is apparent in the adoption of restrictive laws aimed at reducing the number of asylumseekers reaching the border, and increasing the use of harsh detention practices. Moreover among the general public, there is little understanding of the terms refugee, asylum-seeker, economic migrant and illegal migrants. Thus the present paper provides the ever increasing number of world refugee problem and also discusses the issues and challenges of refugees.